1997
DOI: 10.1172/jci119195
|View full text |Cite
|
Sign up to set email alerts
|

von Willebrand factor.

Abstract: A perspective on von Willebrand factor (vWF) 1 within a series on cell adhesion in vascular biology offers the opportunity to review the current understanding of platelet function in hemostasis and thrombosis. Platelets contribute to maintaining the normal circulation of blood through the preservation of vascular integrity and the control of hemorrhage after injury. Thus, the formation of platelet thrombi is a needed defense mechanism, but may precipitate diseases such as myocardial infarction in the setting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
129
1
3

Year Published

1999
1999
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 223 publications
(135 citation statements)
references
References 37 publications
2
129
1
3
Order By: Relevance
“…Platelet adhesion mediated by VWF is rapid and efficient, and the evaluation of the process by video microscopy suggests the rate constants for the binding of A1 to GPIb␣ could be correspondingly fast (19,21,40). However, these studies do not provide direct information about intrinsic dissociation constants or reaction rates, and the results are compatible with other models.…”
mentioning
confidence: 83%
See 1 more Smart Citation
“…Platelet adhesion mediated by VWF is rapid and efficient, and the evaluation of the process by video microscopy suggests the rate constants for the binding of A1 to GPIb␣ could be correspondingly fast (19,21,40). However, these studies do not provide direct information about intrinsic dissociation constants or reaction rates, and the results are compatible with other models.…”
mentioning
confidence: 83%
“…Subsequently, integrin-ligand interactions can mediate stable platelet adhesion. The high efficiency of platelet tethering has suggested that the kinetics of VWF-GPIb binding must be fast and that rapid tethering facilitates the formation of much tighter integrin-dependent bonds that require more time to form (19,21). To date, however, direct measurements of the kinetics of VWF A1-GPIb␣ binding have not been reported.…”
Section: Von Willebrand Factor (Vwf)mentioning
confidence: 99%
“…The platelet-adhesive blood coagulation protein, von Willebrand factor (VWF), is synthesized mainly in vascular endothelial cells (7)(8)(9)(10). VWF is released into plasma as ''unusually large'' multimeric forms (UL-VWFM), highly active in interactions with platelets and collagen (11,12).…”
mentioning
confidence: 99%
“…Besides facilitating the cleavage of vWF by ADAMTS13, fluid shear stress also promotes vWF binding to platelets (19). Binding sites on vWF for platelet GPIb and collagen are in domains A1 and A3, respectively, flanking the ADAMTS13 cleavage site in domain A2.…”
mentioning
confidence: 99%